The Main Tasks of Physical Education of Students in The General Secondary Education System - Robilova Sharofatkhon Mamajon qizi (Zien Journals, 2021)
In this article, physical culture is the first and main type of culture that is formed in a person, understanding the role of sports in human life, work on physical education at school, the main means of physical education in school, the work on the use of natural factors in the physical education of students, and the main tasks of physical education of students in school.
Keywords: Physical Culture; Physical Education; Student; Sports